2015
DOI: 10.1111/bjh.13764
|View full text |Cite
|
Sign up to set email alerts
|

Obinutuzumab (GA101) compared to rituximab significantly enhances cell death and antibody-dependent cytotoxicity and improves overall survival against CD20+ rituximab-sensitive/-resistant Burkitt lymphoma (BL) and precursor B-acute lymphoblastic leukaemia

Abstract: SummaryObinutuzumab is a novel glycoengineered Type-II CD20 monoclonal antibody. CD20 is expressed in approximately 100% of children and adolescents with Burkitt lymphoma (BL) and 40% with precursor B-cell acute lymphoblastic leukaemia (pre-B-ALL). We evaluated the anti-tumour activity of obinutuzumab versus rituximab against rituximab-resistant (Raji 4RH) and -sensitive (Raji) BL and pre-B-ALL (U698-M) cells in vitro and in human BL or Pre-B-ALL xenografted mice. We demonstrated that obinutuzumab compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 43 publications
3
62
0
4
Order By: Relevance
“…As a control, the experiment was therefore repeated with Rituximab, another therapeutic mAb also targeting the CD20 antigen. Rituximab gave similar results, which correspond well with the ongoing search for possibilities to enhance natural killer cell (NK-cell) activity and ADCC response of Anti-CD20 mAbs [31][32][33] and confirms that the assay in principle works.…”
Section: Adcc Response Elicited By Separated Variant Fractionssupporting
confidence: 80%
See 1 more Smart Citation
“…As a control, the experiment was therefore repeated with Rituximab, another therapeutic mAb also targeting the CD20 antigen. Rituximab gave similar results, which correspond well with the ongoing search for possibilities to enhance natural killer cell (NK-cell) activity and ADCC response of Anti-CD20 mAbs [31][32][33] and confirms that the assay in principle works.…”
Section: Adcc Response Elicited By Separated Variant Fractionssupporting
confidence: 80%
“…As a control, the experiment was therefore repeated with Rituximab, another therapeutic mAb also targeting the CD20 antigen. Rituximab gave similar results, which correspond well with the ongoing search for possibilities to enhance natural killer cell (NK-cell) activity and ADCC response of Anti-CD20 mAbs [31][32][33] and confirms that the assay in principle works.For both, Erbitux and Herceptin, a considerably lower EC 50 value was measured for the basic charge variant fraction compared to the main and acidic counterparts, which corresponds to a better performance in the assay. For Herceptin the EC 50 value of fraction B was almost 70% lower compared to fraction M. This means that for this fraction, only one third of the protein concentration is necessary in order to achieve similar lysis activity.…”
supporting
confidence: 80%
“…Furthermore, obinutuzumab was superior in inhibiting growth in NHL xenograft models. 107 Awasthi et al 108 compared obinutuzumab to ritixumab in pre-B-ALL cell lines and found obinutuzumab to be superior in inducing cell death and ADCC. In a pre-B-ALL xenograft model, overall survival was improved with obinutuzumab compared to ritixumab.…”
Section: Future Therapiesmentioning
confidence: 99%
“…Ofatumumab and obinutuzumab (GA101), the latter demonstrated more active than rituximab even in rituximab-resistant BL cell lines, are other anti-CD20 antibodies deserving further evaluation in BL therapy 117. Other most promising new agents are blinatumomab, a bispecific antibody targeting CD19 and bridging CD19+ BL cells to CD3+ cytotoxic autologous T cells, and inotuzumab ozogamicin, an anti-CD22 monoclonal conjugated to calicheamicin.…”
Section: New Drugs and Treatment Modalitiesmentioning
confidence: 99%